2021
DOI: 10.1249/mss.0000000000002680
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training in Patients with Pulmonary Embolism: A Randomized Controlled Trial

Abstract: PurposeHigh-intensity interval training (HIIT) appears to be safe and effective in cardiovascular diseases. However, there is a paucity of data on the effect of HIIT for patients with acute pulmonary embolism (PE). The present randomized controlled trial (RCT) therefore examined the efficiency and safety of HIIT in patients with acute PE.MethodsIn single-center parallel open-label RCT, 24 patients (5 women) discharged recently with a diagnosis of intermediate–high-risk acute PE were randomized (1:1) to supervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Overall, multiple studies have shown that exercise training in patients with PPES is safe. [100][101][102][103][104][105][106][107] Rehabilitation can be effective to improve outcomes of patients with persistent symptoms several months after the acute PE. Randomized controlled trials with large sample sizes investigating the effectiveness of a rehabilitation course in patients with PPES are currently lacking.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, multiple studies have shown that exercise training in patients with PPES is safe. [100][101][102][103][104][105][106][107] Rehabilitation can be effective to improve outcomes of patients with persistent symptoms several months after the acute PE. Randomized controlled trials with large sample sizes investigating the effectiveness of a rehabilitation course in patients with PPES are currently lacking.…”
Section: Treatmentmentioning
confidence: 99%
“…A randomized controlled trial showed significant improvement of estimated VO 2max , RV/left ventricle ratio, and health-related QoL in the high-intensity interval training group after 8 weeks of training started shortly after PE diagnosis, while no improvement was found in the control group. 106 A Danish trial randomized 140 patients between an 8-week home-based exercise program with nurse consultations starting 2 to 3 weeks after PE diagnosis and a control group. The exercise program resulted in a greater improvement of incremental shuttle walk test and PE-specific QoL compared with the control group.…”
Section: Treatmentmentioning
confidence: 99%
“…5 High-intensity interval training in patients with intermediate-high risk PE showed promising results with a marked improvement in the RV/LV diameter ratio after 8 weeks but further larger randomized controlled trials will be needed to confirm these findings and assess long-term benefit. 70 Potential rehabilitative and medical interventions for prevention of post-PE impairment also remain to be studied. Much will depend on a better understanding of post PE impairment pathophysiology and the characteristics of patients at highest risk of developing this complication.…”
Section: Surgical Embolectomymentioning
confidence: 99%
“…These symptoms and functional limitations can therefore be improved with a rehabilitation program that includes exercise. Several studies have investigated the safety and effect of initiating physical exercise after a pulmonary embolism, varying in the study design and interventions that were used [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. The interventions included cardio exercise (running, biking, and fast walking) and these were initiated within a few weeks to several months after the pulmonary embolism was diagnosed, and some included exercise intervals with increased intensity of the program (e.g., bouts of high intensity for 2–3 min several times during each training session).…”
Section: Rehabilitationmentioning
confidence: 99%